2018
DOI: 10.1177/0967010618769812
|View full text |Cite
|
Sign up to set email alerts
|

Spy, track and archive: The temporality of visibility in Eurosur and Jora

Abstract: This article focuses on the temporalities of visibility that is at stake in the functioning of two mapping-monitoring softwares devised by Frontex EUROSUR and JORA. Through a study of border practices and security devices that builds on interviews and direct observation, the article shows that while these systems elaborate on data and information collected in real-time, they work as archives for generating future migration risk scenarios and not for border surveillance purposes. After illustrating in detail th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…As mentioned, the granularity of analysis based on algorithms and big data is changing the way in which security is understood and threats identified and tackled (Aradau & Blanke, 2016). Distributed and mobile technologies are also transforming humanitarian aid (Duffield, 2016; Meier, 2015; United Nations, 2013) and refugees support (Maitland, 2018), while complex technological systems are reshaping borders (Tazzioli, 2018). Social media and distributed platforms have had deep impacts on the formation of public opinions and their circulations, on activism as well as electoral processes—in the last instance on political subjectivities and regimes (Baack, 2015; Dean, 2009; Elwood & Leszczynski, 2012; Luque‐Ayala & Neves Maia, 2018).…”
Section: A “Digital Gap” In Landd Debates?mentioning
confidence: 99%
“…As mentioned, the granularity of analysis based on algorithms and big data is changing the way in which security is understood and threats identified and tackled (Aradau & Blanke, 2016). Distributed and mobile technologies are also transforming humanitarian aid (Duffield, 2016; Meier, 2015; United Nations, 2013) and refugees support (Maitland, 2018), while complex technological systems are reshaping borders (Tazzioli, 2018). Social media and distributed platforms have had deep impacts on the formation of public opinions and their circulations, on activism as well as electoral processes—in the last instance on political subjectivities and regimes (Baack, 2015; Dean, 2009; Elwood & Leszczynski, 2012; Luque‐Ayala & Neves Maia, 2018).…”
Section: A “Digital Gap” In Landd Debates?mentioning
confidence: 99%
“…Alexandra Hall (2017), for example, investigates the decision-making processes of data analysts at a European smart border targeting centre, while Stephan Scheel (2019) was able to observe the practical implementation of a biometric recognition system at consulates and airports. Martina Tazzioli (2018) has, in turn, ethnographically studied how migrant journeys in the Mediterranean Sea are made visible by the European Border Surveillance System (Eurosur).…”
Section: Introductionmentioning
confidence: 99%
“…While in territorial politics and biopolitics the notion of states penetrating or embracing society aptly describes the logic of state power (Torpey 1998: 244-245), viapolitics unfold its ambitions by spying, tracking, and analyzing data on movements and their facilitations (Tazzioli 2018;Broeders/Dijstelbloem 2016;Mountz/ Kempin 2014;Amoore 2009Amoore , 2011. Likewise, EUROSUR does not target migrants, nor does it search for refugees at sea.…”
mentioning
confidence: 99%
“…Going by these proposed descriptions of viapolitics, it can be concluded that the external EU border is strongly governed in the mode of viapolitics -a mode characterized by a projection of power onto the infrastructures and means of movement (and not onto the people that move), a mode determined by a surveillance gaze that tracks and archives (Tazzioli 2018) and which is thus depersonalized and depoliticized. A power oscillating between authoritarian power and humanitarian care, in the sense of being on or off.…”
mentioning
confidence: 99%